2018
DOI: 10.1029/2018ja025557
|View full text |Cite
|
Sign up to set email alerts
|

Response of Different Ion Species to Local Magnetic Dipolarization Inside Geosynchronous Orbit

Abstract: This paper examines how hydrogen, helium, and oxygen (H, He, and O) ion fluxes at 1–1,000 keV typically respond to local magnetic dipolarization inside geosynchronous orbit. We extracted 144 dipolarizations that occurred at magnetic inclination >30° from the 2012–2016 tail seasons' observations of the Van Allen Probes spacecraft and then defined typical flux changes of these ion species by performing a superposed epoch analysis. On average, the dipolarization inside geosynchronous orbit is accompanied by a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
16
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 55 publications
(98 reference statements)
7
16
2
Order By: Relevance
“…The peak probability, 0.93 events per day, takes place at 21 < MLT < 22 and 5 < R XY < 6. Recently, Motoba et al (2018) independently searched the same RBSP data set for sharp dipolarization events and found that the distribution of events skews slightly, but noticeably, more toward midnight than our result, which is presumably because their criterion about the magnetic inclination (>30°) is less…”
Section: Data and Event Selectioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The peak probability, 0.93 events per day, takes place at 21 < MLT < 22 and 5 < R XY < 6. Recently, Motoba et al (2018) independently searched the same RBSP data set for sharp dipolarization events and found that the distribution of events skews slightly, but noticeably, more toward midnight than our result, which is presumably because their criterion about the magnetic inclination (>30°) is less…”
Section: Data and Event Selectioncontrasting
confidence: 71%
“…Second, the correlation between particle injections and local dipolarizations has been known for a long time for geosynchronous altitude (e.g., Erickson et al, ; Sauvaud & Winckler, ), and it can also be statistically confirmed for dipolarizations in the inner magnetosphere (e.g., Motoba et al, ) although there seems to be a certain type of transient (~1‐min) dipolarization, which also tend to take place in the premidnight sector but often without clear particle injections (Liu et al, ). The correlation between dipolarizations and injections is often interpreted as if the injection is an effect of dipolarization; that is, local plasma is energized and transported by the electric field associated with dipolarization.…”
Section: Discussionmentioning
confidence: 97%
“…This is consistent with the present result. Motoba et al () recently examined ion injections inside geosynchronous altitude, and also found that particle behavior is strongly governed by changes in the magnetic field.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The twin Van Allen Probes spacecraft (Mauk et al, ), which are well‐equipped with scientific instruments and have been in operation since August 2012, provide an opportunity to significantly improve understanding of the physical properties of dipolarizations inside GEO and their relation to energetic particles. To the best of our knowledge, only the following three studies, Nosé et al (), Liu et al (), and Motoba et al (, hereinafter referred to as Paper 1), have statistically investigated the dipolarization‐injection relationship inside GEO using Van Allen Probes data. Nosé et al (), who examined 74 dipolarization events that occurred during the first tail season 2012–2013, found (1) that on average magnetic dipolarizations are accompanied by the stronger flux enhancement of oxygen (O) ions at 20–50 keV than hydrogen (H) and (2) that low‐energy (0.1–5 keV) O ion fluxes are enhanced with energy dispersion only near the field‐aligned directions.…”
Section: Introductionmentioning
confidence: 99%